STRATEGI PEMASARAN BAKMI HALAL OIMIE MELALUI APLIKASI GRABFOOD - kenny lee; Kusumawardani, Vidya (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2022)
This research discusses the marketing strategy of a halal noodles vendor Oimie through GrabFood application. This research is conducted to discover the marketing strategies conducted by the halal noodles vendor Oimie in promoting sales through the use of GrabFood application as one of digital alternatives. This research uses a qualitative descriptive method by conducting observation to the research object and also interviewing pre-determined respondents. The data for this research is sourced from a collection of information obtained during observation, documentation, and interview. The research indicates that GrabFood application used by the halal noodles vendor Oimie can actually boost revenue growth through a digital marketing strategy implementation by utilizing the features of GrabFood application. GrabFood’s features that have significant impacts are promotion, menu, and ads. The three features can assist the halal noodles vendor Oimie in promoting sales, creating eye-catching menu displays, and advertising so it can reach prospective consumers and gain profit.